K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

21 tháng 11 2018

Ta có: 5( x + 2 ) - x2- 2x = 0

=> 5x + 10 - x2 - 2x = 0

=> x2 - 3x + 10 = 0

=> (x2 + 2x) - (5x - 10 ) = 0

=> (x-5)(x-2)=0

=> x = 5 hoặc x = 2.

21 tháng 11 2018

\(5\left(x+2\right)-x^2-2x=0\)

\(\Leftrightarrow5x+10-x^2-2x=0\)

\(\Leftrightarrow-x^2+3x+10=0\)

\(\Leftrightarrow-x^2-2x+5x+10=0\)

\(\Leftrightarrow-x\left(x+2\right)+5\left(x+2\right)=0\)

\(\Leftrightarrow\left(x+2\right)\left(5-x\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x+2=0\\5-x=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=-2\\x=5\end{cases}}}\)

20 tháng 10 2021

a) \(PT\Leftrightarrow x^2-4x+1=3x-5\)

\(\Leftrightarrow x^2-7x+6=0\Leftrightarrow\left(x-1\right)\left(x-6\right)=0\Leftrightarrow\orbr{\begin{cases}x=1\\x=6\end{cases}}\)

b) \(PT\Leftrightarrow x^2\left(2x-3\right)-\left(2x-3\right)=0\Leftrightarrow\left(x^2-1\right)\left(2x-3\right)=0\Leftrightarrow x\in\left\{\pm1;\frac{3}{2}\right\}\)

17 tháng 7 2017

Ta có : 3(2x - 1)2 \(\ge0\forall x\)

           7(3y + 5)2 \(\ge0\forall x\)

Mà : 3(2x - 1)2 + 7(3y + 5)2 = 0 

Nên : 3(2x - 1)2 = 7(3y + 5)2 = 0 

\(\Leftrightarrow\hept{\begin{cases}3\left(2x-1\right)^2=0\\7\left(3y+1\right)^2=0\end{cases}}\)

\(\Leftrightarrow\hept{\begin{cases}\left(2x-1\right)^2=0\\\left(3y+1\right)^2=0\end{cases}}\)

\(\Leftrightarrow\hept{\begin{cases}\left(2x-1\right)=0\\\left(3y+1\right)=0\end{cases}}\)

\(\Leftrightarrow\hept{\begin{cases}2x=1\\3y=-1\end{cases}}\)

\(\Leftrightarrow\hept{\begin{cases}x=\frac{1}{2}\\y=-\frac{1}{3}\end{cases}}\)

6 tháng 6 2016

a, \(x^2-25-\left(x+5\right)=0\)

\(\Rightarrow x^2-5^2-\left(x+5\right)=0\)

\(\Rightarrow\left(x-5\right)\times\left(x+5\right)-\left(x+5\right)=0\)

\(\Rightarrow\left(x+5\right)\times\left(x-5-1\right)=0\)

\(\Rightarrow\left(x+5\right)\times\left(x-6\right)=0\)

\(\Rightarrow\hept{\begin{cases}x+5=0\\x-6=0\end{cases}}\)

\(\Rightarrow\hept{\begin{cases}x=0-5=\left(-5\right)\\x=0+6=6\end{cases}}\)

b, \(\left(2x-1\right)^2-\left(4x^2-1\right)=0\)

\(\Rightarrow\left(2x-1\right)^2-\left(\left(2x\right)^2-1^2\right)=0\)

\(\Rightarrow\left(2x-1\right)^2-\left(2x-1\right)\times\left(2x+1\right)=0\)

\(\Rightarrow\left(2x-1\right)\times\left(2x-1-\left(2x+1\right)\right)=0\)

\(\Rightarrow\left(2x-1\right)\times\left(2x-1-2x-1\right)=0\)

\(\Rightarrow\left(2x-1\right)\times\left(-2\right)=0\)\(\Rightarrow\left(-4x\right)+2=0\)

\(\Rightarrow\left(-4x\right)=0-2=-2\)

\(\Rightarrow x=\frac{-2}{-4}=\frac{1}{2}\)

c, \(x^2\times\left(x^2+4\right)-x^2-4=0\)

\(\Rightarrow x^2\times\left(x^2+4\right)-\left(x^2+4\right)=0\)

\(\Rightarrow\left(x^2-1\right)\times\left(x^2+4\right)=0\)

\(\Rightarrow\hept{\begin{cases}x^2-1=0\\x^2+4=0\end{cases}}\)

\(\Rightarrow\hept{\begin{cases}x^2=1\\x^2=\left(-4\right)\end{cases}}\)

\(\Rightarrow x=1\)

20 tháng 12 2020

x2 - 2x - 4 = 0

⇔ ( x2 - 2x + 1 ) - 5 = 0

⇔ ( x - 1 )2 - ( √5 )2 = 0

⇔ ( x - 1 - √5 )( x - 1 + √5 ) = 0

⇔ x = √5 + 1 hoặc x = -√5 + 1

20 tháng 12 2020

\(x^2-2x-4=0\)

\(\Leftrightarrow\left(x^2-2x+1\right)-5=0\)

\(\Leftrightarrow\left(x-1\right)^2-5=0\Leftrightarrow\left(x-1-\sqrt{5}\right)\left(x-1+\sqrt{5}\right)=0\)

\(\Leftrightarrow x=1\pm\sqrt{5}\)

a) Ta có: \(\left(2x+3\right)^2-\left(5+x\right)\left(2x+3\right)=0\)

\(\Leftrightarrow\left(2x+3\right)\left(2x+3+5+x\right)=0\)

\(\Leftrightarrow\left(2x+3\right)\left(3x+8\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}2x+3=0\\3x+8=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}2x=-3\\3x=-8\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\frac{-3}{2}\\x=\frac{-8}{3}\end{matrix}\right.\)

Vậy: \(x\in\left\{\frac{-3}{2};\frac{-8}{3}\right\}\)

b) Ta có: \(\left(2x+5\right)^2-\left(2x-5\right)^2=6x+8\)

\(\Leftrightarrow\left(2x+5+2x-5\right)\left(2x+5-2x+5\right)-6x-8=0\)

\(\Leftrightarrow40x-6x-8=0\)

\(\Leftrightarrow34x=8\)

\(\Leftrightarrow x=\frac{8}{34}=\frac{4}{17}\)

Vậy: \(x=\frac{4}{17}\)

c) Ta có: \(\left(4x+3\right)^2=4\left(x-1\right)^2\)

\(\Leftrightarrow16x^2+24x+9=4\left(x^2-2x+1\right)\)

\(\Leftrightarrow16x^2+24x+9-4x^2+8x-4=0\)

\(\Leftrightarrow12x^2+32x+5=0\)

\(\Leftrightarrow12x^2+2x+30x+5=0\)

\(\Leftrightarrow2x\left(6x+1\right)+5\left(6x+1\right)=0\)

\(\Leftrightarrow\left(6x+1\right)\left(2x+5\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}6x+1=0\\2x+5=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}6x=-1\\2x=-5\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\frac{-1}{6}\\x=\frac{-5}{2}\end{matrix}\right.\)

Vậy: \(x\in\left\{\frac{-1}{6};\frac{-5}{2}\right\}\)

d) Ta có: \(\left(7x-1\right)\left(3x-2\right)-49x^2+14x=1\)

\(\Leftrightarrow\left(7x-1\right)\left(3x-2\right)-\left(49x^2-14x+1\right)=0\)

\(\Leftrightarrow\left(7x-1\right)\left(3x-2\right)-\left(7x-1\right)^2=0\)

\(\Leftrightarrow\left(7x-1\right)\left[3x-2-\left(7x-1\right)\right]=0\)

\(\Leftrightarrow\left(7x-1\right)\left(3x-2-7x+1\right)=0\)

\(\Leftrightarrow\left(7x-1\right)\left(-4x-1\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}7x-1=0\\-4x-1=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}7x=1\\-4x=1\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\frac{1}{7}\\x=\frac{-1}{4}\end{matrix}\right.\)

Vậy: \(x\in\left\{\frac{1}{7};\frac{-1}{4}\right\}\)

9 tháng 7 2019

\(4x^2-81=0\)

\(\Rightarrow\left(2x\right)^2-9^2=0\)

\(\Rightarrow\left(2x-9\right).\left(2x+9\right)=0\)

\(\Rightarrow\orbr{\begin{cases}2x-9=0\\2x+9=0\end{cases}\Rightarrow\orbr{\begin{cases}x=\frac{9}{2}\\x=-\frac{9}{2}\end{cases}}}\)

Vậy ...

\(4x^2-81=0\)

\(\Leftrightarrow\left(2x\right)^2-9^2=0\)

\(\Leftrightarrow\left(2x-9\right)\left(2x+9\right)=0\)

\(2x-9=0\)

\(2x=9\)

\(x=\frac{9}{2}\)

\(2x+9=0\)

\(2x=-9\)

\(x=-\frac{9}{2}\)